2021
DOI: 10.3341/kjo.2021.0013
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of 360° Laser Retinopexy in Patients with Rhegmatogenous Retinal Detachment: a Systematic Review and Meta-analysis

Abstract: Purpose Visual impairment from retinal re-detachment could be debilitating. The aim of this review is to evaluate the role of 360° laser retinopexy on success rate of rhegmatogenous retinal detachment (RRD) repair by a meta-analysis study. Methods The PubMed, Scopus, and the Cochrane Library databases were searched comprehensively from the date of database inception to January 2021, evaluating the role of 360° laser retinopexy in visual and anatomical success rate of RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…In the current study, all operations were performed with 25-gauge instruments. Our finding of no significant differences in surgical outcomes between 360-degree and limited laser retinopexy is incongruent with the hypothesis made by Soekamto et al [ 9 ] that application of 360-degree laser plays a protective role following primary RRD repair using smaller gauge vitrectomy instruments.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In the current study, all operations were performed with 25-gauge instruments. Our finding of no significant differences in surgical outcomes between 360-degree and limited laser retinopexy is incongruent with the hypothesis made by Soekamto et al [ 9 ] that application of 360-degree laser plays a protective role following primary RRD repair using smaller gauge vitrectomy instruments.…”
Section: Discussioncontrasting
confidence: 59%
“…However, the factors associated with its use and the impact on surgical outcomes is not well understood, with conflicting reports in the literature. The theoretical benefit of applying 360-degree laser retinopexy is to seal any missed breaks and barricade any potential anterior re-detachment of the retina [ 4 , 9 ]. However, this must be weighed against the theoretical increased risk of ERM development, postoperative CMO and new tears at laser boundaries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Pars plana vitrectomy has become the most common method of repairing retinal detachments because of its speed, efficacy, and ease of recovery. [2][3][4] Studies have shown that the causes of recurrent retinal detachment after initial PPV repair are missed breaks, opening of old breaks because of persistent or renewed vitreous traction, proliferative vitreoretinopathy, or new break formation. 5 Because of this, research has been directed toward investigating the efficacy of different procedures that can be used as an adjunct during the primary repair to reduce the risk of retinal redetachments.…”
mentioning
confidence: 99%